PENGARUH TEKNIK PENILAIAN PORTOFOLIO DAN SIKAP SISWA TERHADAP HASIL BELAJAR KETERAMPILAN PROSES SAINS SISWA - AFRINAWATI AFRINAWATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
This research aimed to discover the effect of students’ attitude and portfolio assessment in biology towards the achievement of students’ science process skill. The portfolio techniques applied in this research are portfolio process and portfolio product. This research was conducted in 52 and 72 High School in North Jakarta using quasi experiment method. Sample collection used cluster random sampling technique from 42 students. Data was obtained through survey on students’ attitude and academic test achievement. Data was analyzed using two way analysis of variance (ANOVA) by design treatment by level 2 x 2. This research result showed that: (1) achievement of academic test of students’ science process skill that received portfolio assessment technique was higher than the one received product assessment technique, (2) there was an interaction effect between students’ attitude and portofolio assessment, and (3) for students who have positive attitude towards biology, the result of students’ process skill that received portfolio assessment process was higher than the one received product portfolio assessment. The next exsperiment is expected to find a proper assessment techniques for students who have a negative attitude toward biology.